2020
DOI: 10.48550/arxiv.2001.11478
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Direct NMPC for Post-Stall Motion Planning with Fixed-Wing UAVs

Abstract: Fixed-wing unmanned aerial vehicles (UAVs) offer significant performance advantages over rotary-wing UAVs in terms of speed, endurance, and efficiency. However, these vehicles have traditionally been severely limited with regards to maneuverability. In this paper, we present a nonlinear control approach for enabling aerobatic fixed-wing UAVs to maneuver in constrained spaces. Our approach utilizes full-state direct trajectory optimization and a minimalistic, but representative, nonlinear aircraft model to plan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…In some cases, especially in the presence of high winds, NMPC has been utilized to control fixed-wing UAVs [27]. In [1], a receding-horizon NMPC approach was demonstrated that enabled fixed-wing UAVs to execute poststall maneuvers to navigate constrained environments.…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…In some cases, especially in the presence of high winds, NMPC has been utilized to control fixed-wing UAVs [27]. In [1], a receding-horizon NMPC approach was demonstrated that enabled fixed-wing UAVs to execute poststall maneuvers to navigate constrained environments.…”
Section: Related Workmentioning
confidence: 99%
“…Here, we build on the work done in [1] and develop an NMPC-based navigation approach capable of running in realtime using stereo vision. Our method is distinct from other approaches in that it allows seamless exploitation of the full flight envelope for navigation via NMPC, leverages a pointcloud map to maintain a history of sensor data, and provides a means for handling uncertainty in sensor data and state estimates.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations